CAN ARISTOTLE HELP THOMAS NAGEL? - Brinkmann, Klaus (Science et Esprit, 2020)
Aristotle’s teleological principles work inside the individual organism, not as a cosmic principle transcending the boundaries of the species-specific development of individuals. Holding on to the irreducibility of the form, he identifies the mechanisms of efficient causality that give the immaterial final cause a grip on the material substratum. Moreover, his account of biological reproduction in terms of actuality and potentiality does not amount to a scientific theory in our sense, since neither factors are quantifiable. However, Thomas Nagel’s probability requirement, while empirically verifiable, seems not to be a significant advance over Aristotle’s act-potency doctrine, for we still lack the efficient cause. On the whole, then, as far as his biology is concerned, Aristotle seems more like a visionary of modern science than a metaphysician. It is Nagel who seems to have burdened his teleology with a lot of metaphysical commitments that do not harmonize with his intention to preserve the scientific nature of his teleology. A closer look at Aristotle’s analysis of teleological processes in general and his embryology in particular might help us develop a better understanding of how teleology as teleonomy might be a useful scientific hypothesis today.